ANALYSIS OF THE LENGTH AND WEIGHT RELATIONSHIP OF NANGKA SEED FISH (Upeneus vittatus) CAUGHT IN THE WATERS OF IMAM LASTORI PORT, MOROTAI ISLAND DISTRICT - Alwi, Djainudin; Wahab, Iswandi; Safar, Fitriyanti; Rahman, Irfan Hi. Abd (Jurnal Segara, 2024)
Excessive utilization (over-exploited) will have an impact on reducing the productivity of resources including jackfruit seed fish (Upeneus vittatus). This impact causes changes in abundance, productivity and community structure, such as changes in species dominance, size spectra and catch, which results in depletion of stocks and ends in the extinction of this fish population. So far there is no data and information regarding the biological aspects of the morphology of the use of jackfruit seed fish (Upeneus vittatuss) in Morotai Island Regency. The aim of this research is to analyze the relationship between length and weight of jackfruit fish (Upeneus vittatus) caught in the waters of Imam Lastori Harbor, Morotai Island Regency. Data collection was carried out directly in the field (in situ) by measuring the body length and weight of jackfruit seed fish (Upeneus vittatus). The data obtained were analyzed using simple linear regression analysis. The results of a simple linear regression analysis between the total length and weight of the jackfruit fish (Upeneus vittatus) caught in the waters of Imam Lastori harbor obtained the equation: W (weight) = 1.30 x L (length) = 1.35 indicating that for every 1 increase .30 gram units of the weight of jackfruit seeds will increase 1.35 cm units of the length of kuniran jackfruit seeds (Upeneus vittatus). The b value (exponent) of 1.35 indicates a negative allometric growth pattern. This is in accordance with the criteria for the length-weight relationship if the b value <3, then the growth form is negative allometric). Meanwhile, the determination value (R2) obtained was 0.63, meaning that 63% of the increase in fish length was due to the increase in weight (weight) of jackfruit fish (Upeneus vittatus) while 37% was caused by other factors.